Edukasi Pengelolaan Sampah Rumah Tangga Melalui Pelatihan Ecobrick dan Kompos di Dusun I Desa Sibowi - Sabir; Siti Zahra M. Nyombali; Ni Gusti Ayu Anggreni; Nur Aisyah Oktavia; Nur Afifah Umar; Anastia Regina Sampargadi; Hajjaria I Lanyumba; Yuliana; Masyita; Kinasthy; Ni luh Putu Sintia Dewi; Moh. Fajri (LPPM Universitas Widya Nusantara, 2026)
Household waste management remains a problem in Dusun I, Sibowi Village, Tanambulava District, Sigi Regency. This community service program aimed to improve community knowledge and skills in household waste management through education and training on ecobrick and compost production. The methods included health education, discussions, demonstrations, hands-on practice, and evaluation using pre-test and post-test. The results of the activity showed an increase in community knowledge, where good knowledge increased from 0% to 30%, sufficient knowledge increased from 40% to 50%, and poor knowledge decreased from 60% to 20% after participating in the education. Participants were also able to practice making ecobricks and compost as alternative methods of household waste management. These findings indicate that education and practical training are effective in improving community knowledge and skills to support a cleaner and healthier environment.